Unravelling the gut-liver axis: The role of gut microbiota-mitochondria interactions in the pathogenesis and management of metabolic-associated fatty liver disease (MAFLD) - Binzhi Zhang; Xia Luo; Song Lei; Wenbo Gao; Zhipeng Chen; Qing Zhu; Lizheng Huang; Qinqiang Long (Journal of Holistic Integrative Pharmacy)
Metabolic-associated fatty liver disease (MAFLD) has emerged as a prevalent chronic liver disease. Our review of the existing literature reveals that the interplay between gut microbiota, mitochondria, and the liver is a key mechanism in the development of MAFLD. This paper distills the pathogenic role of gut microbiota in MAFLD through its influence on mitochondria and outlines the therapeutic mitochondrial mechanisms of MAFLD that leverage gut microbiota. It also touches on the traditional Chinese medicine perspective on the liver-intestine connection and the concept of ''qi'' in relation to mitochondria, as well as its modern medical counterpart. We conclude that the gut microbiota and their metabolites can directly or indirectly affect the intestinal mitochondria, leading to structural and functional changes. These changes include shifts in mitochondrial membrane potential, changes in permeability, and dysregulation of signaling pathways. As a result, the permeability of intestinal epithelial cells may be increased, and the integrity of the intestinal barrier may be compromised. The gut microbiota and their metabolites can then influence hepatic mitochondria through the hepatic-intestinal axis, triggering liver pathology. When liver damage occurs, their metabolites can enter the intestine and affect intestinal mitochondria and microbiota, which in turn can lead to a disrupted intestinal barrier and microbiota and a dysregulated homeostatic balance. Our extensive literature review suggests that the gut microbiota may mediate the treatment of MAFLD through mitochondrial pathways. The therapeutic approach of modulating the gut microbiota to regulate mitochondrial function and restore liver health is promising. Traditional Chinese medicine diets are particularly well suited for this strategy. Further research is warranted to fully elucidate the underlying mechanisms. By protecting the body's own mitochondrial function through the gut microbiota, we can effectively combat liver injury, providing a novel therapeutic avenue for the treatment of liver disease.